Jenis-Jenis Ikan Hasil Tangkapan dengan Menggunakan Pukat Langga di Tempat Pelelangan Ikan (TPI) Pusong Baru Kecamatan Banda Sakti Pemerintahan Kota Lhokseumawe - Abdullah Abdullah; Dahlian Oesman; Khairiani Khairiani (Biologi Edukasi: Jurnal Ilmiah Pendidikan Biologi, 2009)
A research in fish varieties captured with Langga seine has been conducted at Fishery Auction at Pusong Baru Kecamatan Banda Sakti Lhokseumawe city from 16 to 21 June 2009. The aim of this research is to investigate the varieties of fish captured by fisherman and the population of fish which was under threatened by the usage of Langga seine. This research used survey method with census technique by which the researcher directly visiting Fishery Auction at Pusong Baru Lhokseumawe city. The result showed that there were 73 species of fish classified as 11 Ordos and 31 families. The fish varieties comprised 45 Perciformes ordo from 18 family (62%), 7 Scombriformes Ordo (10%), 5 Clupeiformes Ordo (7%), 4 Scorpaeniformes Ordo (5%), 2 Atheriniformes Ordo (3%), 3 Percessoces Ordo (4%), 2 Pleuronectiformes Ordo (3%), 2 Tetraodontiformes (3%). Meanwhile there was only one species from each ordo Cyprinodontiformes, Siluriformes dan Gadiformes (1%). Perciformes ordo is the most fish varieties found at Fishery Auction at Pusong Baru Lhokseumawe city.